Study of Type 2 Diabetes Mellitus Patients Attending Urban Health Training Centre of Community Medicine Tertiary Care Hospital, Maharashtra - Suchita N Kawale; Manjusha A Shinde; Harshal T Pandve; Prashant S Shinde (Medsci Publications, 2020)
Introduction: Diabetes mellitus is a heterogeneous group of diseases, characterized by chronic hyperglycemia, resulting from environmental and genetic causes. Aim - To study the cases of type 2 diabetes mellitus attending urban health training centre of community medicine department of tertiary care hospital, Maharashtra. Method: It was a hospital based observational descriptive study done in urban health training centre from January to December 2016 including all known cases of type 2 diabetes mellitus which was around 700. Result: Maximum cases were from age group 40-49 years (38.16 %) and 48% were males and 52 % were females. Maximum cases were Hindu 43% having unskilled occupation 19% and nuclear family 46%. Whereas 37% and 18 % study subjects were having BMI of 25- 29.9 and and ≥ 30 respectively, 28 % were having family history of diabetes mellitus, 37% were having Hypertension, 55 % men and 57% women were having abnormal waist-hip ratio, 29 % men and 09 % women were having habit of alcohol intake. Whereas 37% men and 25% women were having habit of tobacco intake. Conclusion: Type 2 diabetes mellitus patients having modifiable and non-modifiable risk factors for the causation of the disease.